Ethnic studies through social psychology lenses: a commentary on plausible perspectives - Adam Assim, Mohd Ibrani Shahrimin (Faculty of Agriculture and Food Sciences, Universiti Putra Malaysia Bintulu Sarawak Campus, 2019)
The current report present a review on some assumptions related to the theoretical lenses of a social psychology framework on ethnic and minority studies. The major implications of selected previous studies are reviewed, as well as some conceptual ambiguities related to the role of social cognition, social interaction and executive functioning of sociocultural planes of analyses in explaining ethnic and minority studies. The constructual validity of a proposed sociocultural framework on a study upon minority Orang Asli children, as well as the limitations of major social psychology theories, is discussed. Discussion is also given to: (a) identifying pertinent denominations in social cognition, (b) incorporating implicit cognition data, and (c) collaborative sociocultural lenses theories into future research practice in ethnic and minorities studies in Malaysia.